Work Volition Scale for Chinese Working Adults: A Cross-Cultural Validation Study. (February 2023) - Lan, Yuanmei; Liu, Doudou; Li, Chaoping; Wang, Jiayan
The present study aims to validate the Chinese version of the Work Volition Scales (WVS), an instrument that assesses three components of work volition: volition, financial constraint, and construct constraint. In Study 1 ( N = 498), the WVS was translated into Chinese, and an exploratory factor analysis (EFA) was conducted resulting in that three factors were consistent with the original scale. In Study 2 ( N = 442), the confirmatory factor analysis showed that the bifactor model provided the most parsimonious fit to the data. The measurement invariance test then revealed that the WVS is equivalent across gender, age, education level, and job tenure. In addition, convergent and concurrent validity supported the finding that the WVS and three subscales are linked with related variables. The results support significant incremental validity in predicting career satisfaction, meaningful work, and life well-being. The findings suggest that the WVS is a valuable instrument for researchers and career counselors who seek to explore work volition among Chinese working adults.